Dimensão do diâmetro e dinâmica de espécies latifoliadas na floresta ombrófila mista sob diferentes intensidades de competição - Loiola, Táscilla Magalhães (2022)
This work was built with the main objective of analyzing and providing infor mation about the dynamics and relationships between broadleaf species with greater ecological importance and Araucaria angustifolia (Bertol.) Kuntze, in face of the environmental conditions of three fragments of Mixed Ombrophilous Forest and , thus , sugge st models for the diameter at the level of trees, growing under competition, using different modeling techniques. The research was carried out in the National Forest of São Francisco de Paula, RS, based on data from the PELD project. Initially, the phytoso ciological characteristics of the study areas were described, and with this it was possible to define the species with the highest value of importance, understood as the species of greater ecological value for the places, from which the target species of t his study were selected and characterized. Then, the environmental attributes of each plot were described using geostatistical techniques, making it possible to visualize the spatial distribution and environmental preferences of the species from ordinary k riging and interpolated maps. The analysis of the mortality and survival of the trees allowed us to infer that the high competitive stress imposed by the dominant trees causedof the death of trees in the lower strata, even young trees, in addition, it was evident that senility also contributed to mortality, as well as the action of climatic events, the factor that contributes to the increase in mortality rates. The morphometric indices made it possible to explain the vitality and stability of the trees of t he 13 species, showing that differences in crown morphometrics are reflected in the variation of the data, as these characteristics change according to the environmental scenario. Larger diameter trees are under a lower level of competition compared to sma ller trees. Among the variables considered for the diameter modeling, height has a significant association with the diameter of trees for 10 species and not significant for three. The canopy descriptor variables present high heterogeneity, however for some of the species the dc variable presented a significant correlation. The competition index selected as the explanatory variable of competition was the Corona and Ferrara Index. There was no regression for the data of the models adjusted for diameter, even with the application of the different techniques. On the other hand, promising results were achieved with the use of artificial intelligence techniques, considering the complexity of the data. The models generated for the competition index did not show reg ression due to the high heterogeneity of the data. Thus, it is recommended to continue researches the premises of sustainable manegement in the FOM, covering more robust management with the advancement of IA in order to guarantee the perpetuity of these ecosystems in future generations.